Corruption Culture on Managing Natural Resources: The Case Political Crime “Papa asking Stock of PT. Freeport Indonesia” - Riyadi, Bambang Slamet; Mustofa, Muhammad (International Journal of Criminology and Sociology, 2022)
This research is the result criminology study on corruption culture of abusing the office and power involved the political elite and state officials in case of ’papa asking the stock’ related to the extension of mining contract of PT. Freeport Indonesia. This research is based on the concept of corruption culture, criminological theories and views of some economic and political observers. The research findings revealed the existence of corruption culture on political crime agreement scenario in case of “Papa Asking The Stock” that are provoking the extension of concentrates export license, diversion of issues and political lobbying to suppress stock divestment and smelter development. The nature of social structures and socio-cultural situations, responses to social situations and relationships with the perpetrators affecting individuals and groups crime behavior. A previous social culture behavior encourages learning in behavior at the society afterwards. State creates the crime laws to protect and maintain its power. The perpetrators rationalize the criminal act on securing and save their interests. Rationalization of corruption culture on the case of ‘papa asking the stocks’ bring forth the law de-penalization mitigating and generating a verdict not guilty to the perpetrators. Corruption culture identical with crime organized state or state crimes against democracy